2021
DOI: 10.1016/j.cmet.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Gut-brain communication by distinct sensory neurons differently controls feeding and glucose metabolism

Abstract: Highlights d Intersectional mapping of sensory neurons identifies distinct gut innervation patterns d Gut-innervating GLP1R+ vagal afferents relay anorexigenic signals to brainstem neurons d Gut-innervating GPR65+ vagal afferent stimulation increases hepatic glucose production d GLP1R+ vagal afferent activity is required to control glycemia during feeding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 87 publications
1
76
0
Order By: Relevance
“…However, bearing in mind the caveats associated with the histology methods employed, it is possible that CCK AP/NTS neurons could also respond to GLP-1R agonists via synaptic inputs. These inputs might include vagal afferent neurons [ 7 , 30 ], AP neurons synapsing onto neighboring NTS neurons [ 31 ], as well as inputs from other central GLP-1RA-responsive cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, bearing in mind the caveats associated with the histology methods employed, it is possible that CCK AP/NTS neurons could also respond to GLP-1R agonists via synaptic inputs. These inputs might include vagal afferent neurons [ 7 , 30 ], AP neurons synapsing onto neighboring NTS neurons [ 31 ], as well as inputs from other central GLP-1RA-responsive cells.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may be explained that in the early stage of AD, the Aβ 42 , especially Aβ 42 monomers or small oligomers from the brain and blood pools, can be easily transmitted through the enteric nervous system (ENS) to the digestive tract of the stomach and intestines. According to reports, the colon contains the most neurons (Gershon, 1998;Rao and Gershon, 2016;Brierley et al, 2018;Borgmann et al, 2021), and the monomers that gradually accumulate in the colon can be aggregated into small molecular weight oligomers. It is worth noting that the colon undergoes vital processes to ensure our health.…”
Section: Discussionmentioning
confidence: 99%
“…The second mode of communication could be due to the existence of GLP-1 receptors on vagal afferent sensitive neurons in the gut. Indeed, Borgmann et al [ 19 ] have shown that the chemogenetic activation of GLP-1 receptor in the intestine reduces glucose levels. Third, GLP-1 receptors are implicated in the activation of hepatic portal vein glucose sensors leading to a decrease in glycemia via an afferent nervous message [ 9 ].…”
Section: Discussionmentioning
confidence: 99%